A Distant View of Close Reading: On Irony and Terrorism around 1977 - Fogarasi György (Hungarian Studies Yearbook, 2019)
In his article “A Distant View of Close Reading: On Irony and Terrorism around 1977,” György Fogarasi investigates the contemporary critical potentials of close reading in the light of recent developments in computation assisted analysis. While rhetorical reading has come to appear outdated in a “digital” era equipped with widgets for massive archival analysis (an era, namely, more keen on “distant,” rather than “close,” reading), Paul de Man’s insights concerning irony might prove useful in trying to account for the difficulties we must face in a world increasingly permeated with dissimulative forms of threat and violence. The article draws on three major texts from 1977: de Man’s draft on “Literature Z,” his lecture on “The Concept of Irony,” and the first and second Geneva Protocols. The reading of these texts purports to demonstrate the relevance of de Man’s theory of irony with respect to the epistemology of “terrorism,” but it also serves as an occasion to reflect upon questions of distance, speed, range, scale, or frequency, and the chances of “rhythmanalysis.”